2014
DOI: 10.1007/s00360-014-0852-x
|View full text |Cite
|
Sign up to set email alerts
|

Dietary effect on immunological energetics in mice

Abstract: Defense against natural aggressors, such as bacterial infections, requires both energy and an immune-cellular response. However, the question as to how these two components are interconnected in small endotherms by means of the host diet remains only poorly understood. Here, we tested in laboratory mice whether dietary proteins and carbohydrates can modulate the interplay between energy expenditure, food intake and the innate and adaptive immune response when confronting a bacterial challenge (Bacillus Calmett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…While this investment could partially close the gap in protein acquisition between treatments, consumption would need to be 400% higher in the LP treatment to achieve similar protein levels to individuals on the HP diet. However, dietary protein does not affect host metabolic rate ( 16 ), so maintenance costs (Figure 1 ) are likely similar between treatments. Insects were also present in the enclosures and diet metabarcoding tools could be used in future studies to examine if, and to what degree, lab mice are able to utilize them as a food source.…”
Section: Discussionmentioning
confidence: 99%
“…While this investment could partially close the gap in protein acquisition between treatments, consumption would need to be 400% higher in the LP treatment to achieve similar protein levels to individuals on the HP diet. However, dietary protein does not affect host metabolic rate ( 16 ), so maintenance costs (Figure 1 ) are likely similar between treatments. Insects were also present in the enclosures and diet metabarcoding tools could be used in future studies to examine if, and to what degree, lab mice are able to utilize them as a food source.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings add to this growing body of research by suggesting that the effect of diet depends on the variables analyzed; however, we cannot abandon the possibility of the effect of a more extreme diet on the immune system development. Other studies have reported that diets with a greater difference in the amount of proteins (~45%) resulted in effects on the immune response in adult mice (Martel et al, 2014). On the other hand, it is essential to study the relationship of fiber content of diet and the variables analyzed here.…”
Section: Discussionmentioning
confidence: 97%
“…Dietary quality is an essential factor that influences the maintenance and functioning of the immune system of animals (Catalán et al, 2011; De Coster et al, 2011; Klasing, 2007; Venesky et al, 2012). For instance, the amount of dietary protein has been related to the magnitude of the immune response of some endothermic species (Bounous et al, 1983; Jennings et al, 1992; Li et al, 2007; Martel et al, 2014). Specifically, diets with low‐protein content are related to suppression of the immune response (Jennings et al, 1992; Li et al, 2007; Venesky et al, 2012).…”
Section: Introductionmentioning
confidence: 99%